2019
DOI: 10.1007/s10068-019-00590-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maillard reaction on physicochemical and functional properties of walnut protein isolate

Abstract: In this study, the Maillard reaction (MR) of glucose was applied to improve the physicochemical and functional properties of walnut protein isolate (WNPI). The MR products (MRPs) were prepared with glucose at 0 h (MRP0), 1 h (MRP1), 2 h (MRP2) and 3 h (MRP3) heating at 95°C. The Infra-Red spectrum showed reduction of amide and S-H functionalities in MRPs with complete intermixing of glucose in MRP3. Scanning electron microscopy indicated changes in the morphology of MRP3 which also exhibited promising antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Increases of walnut protein isolate in emulsifying activity and emulsion stability were observed after glycosylation by glucose (Ullah et al, 2019), as well as the solubility of canola protein isolate at isoelectric point by gum Arabic (Pirestani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increases of walnut protein isolate in emulsifying activity and emulsion stability were observed after glycosylation by glucose (Ullah et al, 2019), as well as the solubility of canola protein isolate at isoelectric point by gum Arabic (Pirestani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…as well as antioxidant properties, they attracted interest to be used for the encapsulation of bioactive materials. Simultaneous increases of emulsifying properties and antioxidant activity upon glycation were observed for partially hydrolyzed soy protein isolate with maltodextrin [145], pea protein isolate with gum arabic [178], the soluble fraction of pea protein isolate with dextran [183], walnut protein isolate with glucose [251], and partially hydrolyzed black bean protein isolate with glucose [190]. These findings can be useful for the future development of encapsulation systems for hydrophobic, oxidation-sensitive compounds.…”
Section: Encapsulationmentioning
confidence: 72%
“…Another example are walnut proteins which can be recovered from defatted walnut flour after oil extraction. Their glycation with glucose improved their emulsifying activity and stability and led to promising antioxidant properties [251]. Further examples for glycation studies on less utilized plant proteins can be found in Table 4.…”
Section: Othermentioning
confidence: 99%
“…Another example is walnut proteins, which can be recovered from defatted walnut flour after oil extraction. Their glycation with glucose improved their emulsifying activity and stability and led to promising antioxidant properties [ 254 ]. Further examples for glycation studies on less utilized plant proteins can be found in Table 4 .…”
Section: Glycation Of Major Plant Proteinsmentioning
confidence: 99%
“…Since glycated plant proteins show high solubility, excellent emulsification activity, and stability (see Section 5.1 ), as well as antioxidant properties, their use in the encapsulation of bioactive materials has attracted interest. Simultaneous increases in emulsifying properties and antioxidant activity upon glycation were observed for partially hydrolyzed soy protein isolate with maltodextrin [ 146 ], pea protein isolate with gum arabic [ 179 ], the soluble fraction of pea protein isolate with dextran [ 184 ], walnut protein isolate with glucose [ 254 ], and partially hydrolyzed black bean protein isolate with glucose [ 191 ]. These findings could be useful in the future development of encapsulation systems for hydrophobic, oxidation-sensitive compounds.…”
Section: Functional Properties and Potential Applications Of Glycamentioning
confidence: 99%